PENGARUH PERISTIWA POLITIK TAHUN 2019 (PEMILU PRESIDEN DAN PENGUMUMAN SUSUNAN KABINET) TERHADAP SAHAM SEKTOR INDUSTRI DI BURSA EFEK INDONESIA - Jamaludin Anwar; Nur Diana; M. Cholid Mawardi (Universitas Islam Malang, 2020)
Political events are one of some causes that influence investment activities in the capital market. The purpose of this research is to find out the Effect of Political Events on Industrial Sector Shares in 2019. As one of the main sectors affecting the stock market on the Indonesia Stock Exchange (IDX). The data used secondary data from CSPI and industry sector daily trading. This study used 84 samples companies that have been selected through purposive metode for 14 days presidential election event period, and 14 days announcement of the cabinet event period. The results that the presidential election event was able to influence the trading volume of industrial sector shares, although there was no abnormal return that occurred in that event. While the cabinet announcement event showed zero results (no influence whatsoever) on trade in industrial sector shares that occurred on the Indonesia Stock Exchange. Keywords : Political Events, Capital Market, Presidential Election, Cabinet Announcement, Abnormal Return, Trading Volume Activity, Event study